Cancer testis antigens in newly diagnosed and relapse multiple myeloma: prognostic markers and potential targets for immunotherapy - Duin, Mark van; Broyl, Annemiek; Knegt, Yvonne de; Goldschmidt, Hartmut; Richardson, Paul G.; Hop, Wim C. J.; Holt, Bronno van der; Joseph-Pietras, Debora; Mulligan, George; Neuwirth, Rachel; Sahota, Surinder S.; Sonneveld, Pieter (Haematologica, the hematology journal, 2011)
Background In multiple myeloma, expression of cancer testis antigens may provide prognostic markers and potential targets for immunotherapy. Expression at relapse has not yet been evaluated for a large panel of cancer testis antigens which can be classified by varying expression in normal tissue: restricted to testis, expressed in testis and brain and not restricted but selectively expressed in testis.Design and Methods Evaluation of cancer testis antigen expression was made in newly diagnosed multiple myeloma cases (HOVON-65/GMMG-HD4 trial; n=320) and in relapse cases (APEX, SUMMIT, CREST trials; n=264). Presence of expression using Affymetrix GeneChips was determined for 123 cancer testis antigens. Of these 87 had a frequency of more than 5% in the newly diagnosed and relapsed patients, and were evaluated in detail.Results Tissue restriction was known for 58 out of 87 cancer testis antigens. A significantly lower frequency of presence calls in the relapsed compared to newly diagnosed cases was found for 3 out of 13 testis restricted genes, 2 out of 7 testis/brain restricted genes, and 17 out of 38 testis selective genes. MAGEC1, MAGEB2 and SSX1 were the most frequent testis-restricted cancer testis antigens in both data sets. Multivariate analysis demonstrated that presence of MAGEA6 and CDCA1 were clearly associated with shorter progression free survival, and presence of MAGEA9 with shorter overall survival in the set of newly diagnosed cases. In the set of relapse cases, presence of CTAG2 was associated with shorter progression free survival and presence of SSX1 with shorter overall survival.Conclusions Relapsed multiple myeloma reveals extensive cancer testis antigen expression. Cancer testis antigens are confirmed as useful prognostic markers in newly diagnosed multiple myeloma patients and in relapsed multiple myeloma patients.The HOVON-65/GMMG-HD4 trial is registered under Dutch trial register n. NTR-213. CREST, SUMMIT and APEX trials were registered under ns. M34100-024, M34100-025 and NCT00049478/NCT00048230, respectively.